The Shabti of the Lady of the House Iahhetep and the Emergence of Female Shabtis in the New Kingdom - Glanzmann, Rahel (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
This paper is divided into two main sections. The first section represents the publication of a shabti preserved in the Musée du Louvre in Paris (Inv. No. E 3088). This shabti belonged to a Lady of the House named Iahhetep. It dates to the 18 th Dynasty under Pharaoh Thutmosis III. It is notable because it is one of the first known shabtis to exhibit female features in its outer appearance: the Hathor wig. The second section of this paper deals with female shabtis in general. It illustrates their iconographic variety and outlines their role as transitional figurines within the movement from mummiform shabtis towards the production of shabtis in the dress of daily life. Furthermore, female shabtis may have served as a vehicle of the owner’s self-presentation and may thus be regarded as a manifestation of the self-confidence and self-awareness of elite women of the period.